EFEKTIVITAS PENGGUNAAN MULTIMEDIA AUTO PLAY ETNIK KALIMANTAN TIMUR TERHADAP HASIL BELAJAR MATEMATIKA SD FASTABIQUL KHAIRAT KELAS VI DI KOTA SAMARINDA - Razak, Abdul; Rumainur, Rumainur (JMIE (Journal of Madrasah Ibtidaiyah Education), 2018)
The research objective is to find out the effectiveness of Mathematics learning result by using multimedia auto play of East Kalimantan ethnic. The research is a quasi-experimental with pretest-posttest control group design. The population of the research is all sixth grade students of SD Fastabiqul Khairat in Samarinda City. The data collection technique is done by simple random sampling. The research sample is 50 students consist of 25 students for experimental and control groups. The instrument used in collecting the data is the test of Mathematics learning result. The prerequisite of data analysis is using Liliefors test for the normality test while for homogenity test is using Fisher test, with a = 0,05 obtained the sample from the normal and homogeneous distribution of population, while the data analysis technique is using t test. The research result is that the using of multimedia auto play of East Kalimantan ethnic is effective in increasing the Mathematics learnning result.